Empowering Social Competence in Reflective Teaching: An Empirical Research of Madrasah Ibtidaiyyah (Islamic State Elementary School) in Indonesia - Zainuri, Ahmad; Huda, Miftachul; Maseleno, Andino (International Journal of Psychosocial Rehabilitation, 2020)
The main problem of this research is to examine the level of social competence of teachers in the Madrasah Ibtidaiyah (Islamic State Elementary School) in Palembang, Indonesia. This is expected to be useful as a research material for the management of Palembang City MIN and other stakeholders and stakeholders. Therefore, this type of research is field research with the MIN population of the city of Palembang. All members of the population are numbered into 85 teachers as respondents. Data collection was conducted through questionnaire techniques, interviews, observation, and documentation study. Furthermore, the data were analysed by descriptive statistical techniques. The assessment is done by a Likert scale, which is a scale used to measure attitudes, opinions, and perceptions of a person or group of people about the research variable. With a Likert Scale, the variables to be measured are translated into variable indicators. Then, the indicator is used as a starting point for compiling instrument items which can be in the form of statements or questions. The answer to each instrument item using the Likert scale has gradations from very positive to very negative, which can be in the form of words; sting good, good, enough, less and less good. Based on the overall description in the study it was found that the social competencies of the Madrasah Ibtidaiyah (MI) teachers in Palembang were in a good category (mean score 299.5). This social competence is the only one of the four teacher competencies in the good category. This is due to all dimensions of social competence, namely: (a) being inclusive, acting objectively, and not discriminatory because of consideration of gender, religion, race, physical condition, family background, and socio-economic status; (b) communicating effectively, empathically, and politely with fellow educators, education staff, parents and the community; (c) Adapt in the place of duty throughout the territory of the Republic of Indonesia that has socio-cultural diversity, and (d) Communicate with the professional community itself and other professions verbally and in writing or other forms, in good categories. Teachers with good social competence will have a high awareness to foster their students, so that they have the same social competence in facing the world of the future and their profession. In line with that, the teachers must develop a learning process that simultaneously trains students’ social competencies through the following steps: Give the opportunity to students to ask fellow friends, and also to teachers, so that they have the skills to communicate with others. Develop class discussions on topics that are appropriate for their age development.